A confirmatory analysis of zakah compliance behavioural intention on employment income - Bidin, Zainol; Md. Idris, Kamil (Universiti Utara Malaysia, 2007)
A confirmatory test of Ajzen and Fishbein’s (1980) theory of reasoned action using structural equation modeling was carried out to study the impact of zakah compliance intention toward employment income. This study had two objectives: 1) to examine the reliability and validity of all variables in the theory of reasoned action using confirmatory factor analysis (CFA), and 2) to determine the relationship between each variable of attitude and subjective norm (obtained from CFA) with zakah compliance intention on employment income. Based on 264 respondents, we used CFA structural equation modeling as the measurement model in measuring attitude, subjective norm, and intention. This study used decomposition of variable in the theory of reasoned action to analyse zakah compliance intention of zakah on employment income. The results of the study indicated that the goodness of fit model comprising attitude, subjective norm, and intention is better when CFA was used. Three components of attitude and two components of subjective norm constructs were found to achieve unidimensionality, and convergent validity and discriminant validity. Thus, this study supported the argument that attitude and subjective norm in the model of zakah on employment income compose of several components and provide good reliability and validity if each component is tested with CFA. Additionally, this study also supported the relationship between attitude and subjective norm with zakah compliance behavioural intention. Recommendations for practice and limitations of the study are also discussed.